Research Results on Survival Rate for Postoperative Colon Cancer Surgery - Rentsenbalbar, Ganbaatar; Munkhjargal, Chinzorig; Nachin, Baasanjav (Central Asian Journal of Medical Sciences, 2022)
Objective: Although the incidence of colorectal cancer is relatively low in Mongolia, the postoperative survival rate has not been fully studied. Thus, we have aimed in the present study to analyze the survival rate after surgical treatment of colorectal cancer. Methods: We studied the patient history of all patients who underwent surgery in the General Surgery Department, National Cancer Center of Mongolia from January 2013 to December 2015 and evaluated the results. Results: The average survival rate of all patients was 42 months or 95 %. In patients with colorectal cancer, the 5-year survival rate after surgery was 59.3 %. By stages, the percentage of patients diagnosed in stage I was 100 %, in stage II 75 %, in stage III 64.4 %, and in stage IV 12.5 %, and the survival rate varied from stage to stage. It was also found that early diagnosis was directly related to survival rate (p = 0.000). Furthermore, the outcome of postoperative chemotherapy had a direct effect on the postoperative survival rate (p = 0.000). The average survival rate is 1280 days 1172.7 - 1389.06 (95 % conf. Interval), 42 months 38.5 - 45.6 (95 % conf. Interval), 3.5 years 3.2 - 3.8 (95 % conf. Interval), which was relatively high compared to other cases of cancer. In addition, the survival time is statistically related to the outcome of surgery and postoperative treatment (p = 0.000). Conclusion: The results of our study show that viability decreases statistically in later stages of cancer manifestation.